Аналіз ролі плаваючих броньованих машин у бойових умовах - Агапов, Олег Миколайович; Краснокутський, Володимир Миколайович; Зінченко, Олена Іванівна (Національний технічний університет "Харківський політехнічний інститут", 2025)
Розкриття теми статті проведено з точки зору історичного контексту: розглянуто еволюційний шлях розвитку плаваючих броньованих машин від перших зразків до сучасних виробів з аналізом їх ролі на кожному етапі. Вказані основні завдання, які повинні виконувати плаваючі броньовані машини. Проведений аналіз застосування плаваючих броньованих машин у військових умовах різного масштабу з метою визначення перспективи їхнього розвитку. Показано, що створення надійної та ефективної плаваючої військової машини є складним інженерним завданням, що вимагає застосування спеціальних матеріалів, конструктивних рішень і технологій, а також супроводжується складнощами і багатьма суперечливостями. Складність і суперечливість вимог до плаваючих броньованих машин підтверджується кількістю невдалих проєктів у світі, які починалися, але не були доведені до кінця. Сучасна війна виявила роль і завдання плаваючих броньованих машин, а також якість кожної машини, поставленої союзниками Україні. Окремо проаналізовано амфібійні плаваючі броньовані машин, які є основним елементом при проведенні морських десантних операцій. Зроблено висновки про роль плаваючих броньованих машин у військових умовах і можливі перспективи їх розвитку. The topic of the article is discussed from the point of view of historical context: the evolutionary path of development of floating armored vehicles from the first samples to modern products is considered with an analysis of their role at each stage. The main tasks that floating armored vehicles must perform are indicated. The application of floating armored vehicles in military conditions of various scales was analyzed in order to determine the prospects for their development. It was shown that the creation of a reliable and effective floating military vehicle is a complex engineering task that requires the use of special materials, design solutions and technologies, and is also accompanied by difficulties and many contradictions. The complexity and contradiction of floating armored vehicles requirements is confirmed by the number of unsuccessful projects in the world that were started but not completed. Modern warfare has revealed the role and tasks of floating armored vehicles, as well as the quality of each vehicle supplied by the allies to Ukraine. Amphibious floating armored vehicles, which are the main element in conducting naval landing operations, are separately analyzed. It is stated that they have made significant progress by increasing water speed and security. Conclusions are drawn about the role of floating armored vehicles in military conditions and possible prospects for their development. In particular, active work is underway to implement unmanned technologies in the tactics of using floating armored vehicles.
Analysis of the role of floating armored vehicles in combat conditions
Keywords: плаваючі броньовані машини; амфібійні машини; десантні операції; гребневі винти; водомети; протипульне бронювання; floating armored vehicles; amphibious vehicles; amphibious operations; propellers; water cannons; bulletproof armor